(untitled) (Academicia Globe: Inderscience Research, 2023)
The article provides information on how to effectively use design and problem-based learning methods when teaching a programming language. Information is provided about the methods of teaching the programming language and their differences, about the work of scientists who carried out scientific activities based on these methods. Examples of projects executed in the Python programming language are based on design and problem-based learning.